The Li-Yorke Chaos in quadratic stochastic Volterra operators - Saburov, Mansoor (2012)
This paper is written in the framework of the Author's previous papers. The dynamics of quadratic stochastic Volterra operators (in short Volterra QSO) was deeply studied. However, we can still observe some chaotic behaviors of such operators. In this paper, we provide a criterion for an existence of the Li-Yorke chaos in a class of Volterra QSO acting on a finite dimensional simplex.